(NsOBRANIE SO^INENIJ W [ESTI TOMAH (B/s (N~ASTX (B4s - (NlESKOW(B, (Nn(B.(Nss ((NmOSKWA(B:s (NpRAWDA(B,s, 1973)
(Nw (B4 (NTOM sOBRANIQ SO^INENIJ WO[LI PROIZWEDENIQ PISATELQ TAKIE KAK (B"(NbELYJ OREL(B", "(NlEW[A(B" (NI MNOGIE DRUGIE RAZNYH VANROW(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs; (NfANTASTIKAs